(untitled) (Journal of Business Management and Accounting, 2022)
Food production in Nigeria depends largely on subsistence farmers in the rural areas, where inefficient transport system remains a serious challenge and threat to food security in the country. This paper examines the effect of road transport system in the rural areas on food security in Akinyele Local Government Area of Oyo State, Nigeria. The study adopts a descriptive analysis, Multicollinearity and Cronbach Alpha Reliability tests as well as regression analysis on the primary data. Findings from the study reveal through the multicollinearity test, absence of significant correlation among the independent variables and the Cronbach Alpha confirms internal consistency of the variables. Furthermore, the regression analysis indicates that transportation infrastructure has a positive and statistically significant effect on food security. More so, rural development and road network show positive significant effect on food security. Meanwhile, Market infrastructure and Security issues are not statistically significant to explain variations in food security. The paper therefore, recommends that governments should extend efficient road transport to the rural areas to facilitate the movement of agricultural produce from the village to the market and the industries. This will help to reduce wastes resulting from damage of farm produce due to the long distance to the city.